THE EFFECT OF FINANCIAL PERFORMANCE, CASH HOLDING, AND TAX AVOIDANCE ON INCOME SMOOTHING WITH COMPANY GROWTH AS A CONTROL VARIABLE - Nurisma Amelia; Mirna Amirya (FEB-Telkom University Publisher, 2026)
This study aims to determine the effects of financial performance, cash holdings, and tax avoidance on income smoothing, with company growth as a control variable. In this study, income smoothing is measured using the Eckel index, while financial performance is proxied by Return on Assets (ROA) to measure profitability and by the Debt to Equity Ratio (DER) to measure leverage. From a population of 93 property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2023 period, 22 were selected as samples using purposive sampling, yielding 88 observations. Using logistic regression, this study finds that financial performance, as measured by profitability, has a negative effect on income smoothing, while financial performance, as measured by leverage, along with cash holding and tax avoidance, does not affect income smoothing. The results of this study indicate that profitability, as measured by ROA, is a factor influencing income smoothing practices. In practice, these findings may be a consideration for investors and regulators in assessing the potential for income-smoothing practices, given greater attention to the company’s profitability